CULTURAL ADAPTATION IN PARENTING COUNSELING PROGRAMS: EXPLORING BEST PRACTICES FOR MULTICULTURAL FAMILIES IN RURAL COMMUNITIES - Tristiyanto, Edy; Zuhriyah, Nabilaa Faizatuz; Alifah, Nur (Islamic Counseling and Parenting Journal, 2024)
Multicultural families in rural communities face unique challenges in parenting due to differences in cultural values, language, and gender role perceptions. Parenting counseling programs that do not consider multicultural aspects often exacerbate conflicts in families. Therefore, this study aims to explore best practices in culture-based parenting counseling for multicultural families in rural communities. This study used a qualitative approach with a case study design. Data were collected through in-depth interviews, participant observation, and documentation with 10 multicultural families and 5 counselors. Thematic analysis was used to identify key themes of cultural adaptation challenges and practices. The results showed that the main challenges faced by multicultural families were differences in cultural values (45%), language barriers (25%), and differences in gender role perceptions (20%). Open communication practices and empathy-based approaches have proven effective in helping families overcome these differences. Counselors have an important role as mediators in helping multicultural families unite different cultural values in harmonious parenting patterns. This study recommends counselor training to increase cultural sensitivity and the development of counseling programs that are adaptive to cultural differences in rural communities.